The Role of Comorbidities in the Development of Bronchopulmonary Diseases in Military Personnel (Texas Journal of Medical Science, 2026)
This study investigates the role of comorbidities in the course of bronchopulmonary diseases among military personnel. Comorbid conditions were identified in 59.3% of patients. The most common were gastrointestinal diseases (37.7%), cardiovascular diseases (10.6%), kidney diseases (7.7%), and diabetes mellitus (3.3%). Cardiovascular diseases (OR=19.6; p